An Experimental Investigation of Mobile Commerce (M-Commerce) Payment Systems: A Case of UUM MBA Students. - Abdussalam, Ashraf (2007)
Micro payments systems are the important model for m-commerce application and implementations especially in ICT environment of Malaysia. This is because of m-commerce fasters growing area which has a huge potential in the up coming era. So, this study will be investigating the benefits, m-commerce payment environment, and services satisfaction on m-commerce providers. Issues related to micro payment system for m-commerce also discuss especially form MBA student's perspectives. The main objective of this study is; (a) to determine the level of m-commerce among students in UUM; (b) to determine the level of m-commerce payment system among students in UUM;(c) to determine the level of m-commerce payment environment among students in UUM; and (d) to examine the relationship between payment system and payment environment toward m-commerce services satisfaction. Case studies based on MBA's UUM student were conducted. So that, investigation and exploration approaches were employed to search the insights of M-Commerce payment methods.